Four new white flesh and freestone peaches - Ojima, Mário; Dall'Orto, Fernando A. Campo; Rigitano, Orlando; Scaranari, Hélio J.; Martins, Fernando P.; Tombolato, Antonio F. C.; Garbosa, Wilson (Pesquisa Agropecuaria Brasileira, 2014)
'Jóia-l' (IAC 771-1), 'Jóia-2' (IAC 471-1), 'Doçura-2' (IAC 2370-3) and Doçura-3' (IAC 1571-2) are four new white-flesh dessert peaches, selected for adaptation to the mild winter climatic conditions prevailing in the State of São Paulo, Brazil. They resulted from crosses between some local peach cultivars with peaches and nectarines introduced from Florida, USA. Their most important characteristics besides low chilling requirement are great tree vigour, early ripening, and high productiveness, and excellent taste quality.